Changes in the Suicide Rate under the Influence of Daily Activities in EU Countries - P. A. Korotkov; A. B. Trubyanov; E. A. Zagaynova; A. I. Zverev (Статистика и экономика)
The article examines the impact of daily activities on the suicide rate on the basis of data from the European Detailed Mortality Database of the World Health Organization and the Harmonized European Time Use Survey.Purpose. To evaluate the relation between the suicide rate and duration of the main daily activities of employees in the spheres of work, household and leisure activities in terms of the multifactor models. Materials and methods. Daily activities are understood as time spent on work, household and leisure activities. In order to analyze the relation between the variables an end-to-end linear regression model arranged by all years and countries is used; the panel data structures are not taken into account in the model (as we have to deal with pseudo panel data). In addition, in order to weaken prerequisites of parametric models, a non-parametric estimate is used. The calculations are made in the econometric package STATA IC 16. The source of the data on the suicide rate (total, men, women) at the ages of 15-74 is the European Detailed Mortality Database of the World Health Organization; the source of the data on time spent on the main daily activities of employees in the spheres of work, household and leisure activities and the level of employees’ occupation is Eurostat.Results. The analysis revealed that with the increase in time spent on TV and video the suicide rate increases for the employed men; and with the increase in time spent on housekeeping the suicide rate increases for the employed women. In addition, during working days employed men are expected to be at risk of suicide due to the time spent on work, related activities and travel to and from work; employed women remain at risk due to the time spent on housekeeping. The duration of TV and video watching and housekeeping is a referent of suicide risk factors – loneliness and retreat from the society. It has been established that a possible shift to a four-day working week with an increase in the working hours while maintaining weekly hours leads to the suicide rate increase. Conclusion. In order to reduce the suicide rate in European countries, it is necessary to have such an organization of labour, daily routine and leisure activities, which will allow male employees to reduce their working hours to a minimum of 7.4 hours and to displace watching TV and video on the periphery of the hierarchy of occupations, primarily on weekends, as well as to eradicate "kitchen slavery" among female employees. While evaluating the possible shift to a four-day working week, it is necessary to conduct more research on the impact of the number (ratio) of working days and full days off on the suicide rate.